Experimental investigation of the morphology of salt deposits from drying sessile droplets by white-light interferometry - Sondej, Franziska; Peglow, Mirko; Bück, Andreas; Tsotsas, Evangelos (AIChE Journal, 2018)
This study presents a new approach to investigate the drying behavior and the structure of deposit resulting from drying of solid containing micro droplets. It is shown that deposit structure (porosity and “footprint”) depends on drying conditions. This dependency may contribute to better understanding of particle‐forming processes, such as fluidized bed coating. In the framework of this study, sessile droplets containing sodium benzoate dissolved in water were dried on thin glass plates in a small drying chamber. The drying conditions (temperature, moisture content and flow rate of drying gas) and material parameters (solid content of solution) were systematically varied. The drying rate of droplets was determined from the moisture balance of the drying gas. The final three‐dimensional shape of dried sessile droplets was measured using white‐light interferometry and transformed into a two‐dimensional profile using a Monte Carlo method. Moreover the mean porosity of dried droplets was calculated. By comparison of structural information and process conditions it is shown that the drying process may have a large influence on deposit structur
Keywords: Monte Carlo evaluation; salt solutions; drying chamber; structural analysis; white-light interferometry; sessile droplet drying; solid deposit